Improving Financial Report Quality Through Good Governance and Government Accounting Standards in Berau Regency - Siti Munawaroh; Sayugo Adi Purwanto; Djupiansyah Ganie; Caetano Carceres Correia (International Journal of Economics and Management Research, 2025)
This research explored the influence of Good Governance and Government Accounting Standards on the quality of financial reports Management Agency and Regional Assets of Berau Regency. Primary data were collected through questionnaires distributed to 60 respondents who were employees of the BPKAD of Berau Regency and used as research samples. "The analysis, which included several statistical tests, yielded significant insights and conclusions about the study's focus. 1) Good governance significantly enhances financial report quality in Berau Regency's financial management 2) Government Accounting Standards significantly impact financial report quality in Berau Regency. 3) Good governance and SAP, when implemented together, substantially improve financial reporting quality